2016
DOI: 10.1364/boe.7.004490
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coherence length, signal-to-noise ratio, log transform, and low-pass filtering on layer thickness assessment with OCT in the retina

Abstract: Optical coherence tomography (OCT) images of the retina are inevitably affected by the finite width of the coherence function and noise. To make low-reflective layers visible, the raw OCT signal is log transformed; to reduce the effect of noise the images can be low-pass filtered. We determined the effects of these operations on layer thickness assessment, as a function of signal-to-noise ratio (SNR), by performing measurements in a phantom eye and modeling. The log transform appeared to be the key factor in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Most of the subjects included in our study were young myopic subjects (Table 1 ). It has been reported that the image quality of OCT scans affects the observed retinal layer thicknesses 37 39 , and image quality decreases with an increase in myopia 40 . Consistent with Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the subjects included in our study were young myopic subjects (Table 1 ). It has been reported that the image quality of OCT scans affects the observed retinal layer thicknesses 37 39 , and image quality decreases with an increase in myopia 40 . Consistent with Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, thickness measurements of low-reflective layers underestimate the real thickness. This over-and underestimation are less pronounced, and should theoretically disappear completely, if the analysis is based on linear-scale images [19]. The phantom layer addressed in the current study is neither a high-reflective nor a low-reflective layer, but is preceded by a layer with a lower reflectivity and followed by a layer with higher reflectivity [Figs.…”
Section: Discussionmentioning
confidence: 77%
“…Images may also be compressed to fit the commonly used 8-bit depth of monitors. In order to get unbiased thickness estimates, however, the untransformed, referred to as linear-scaled image in this article, data are needed [19].…”
Section: Discussionmentioning
confidence: 99%
“…retina could be carefully be quantified, again of a large area around the optic nerve. Recent measurements on a retinal phantom however, have shown that these measurements may not be reliable [8][9][10] , as the thickness of the retinal nerve fiber layer cannot be determined reliably. Another issue is caused by glial content.…”
Section: Introductionmentioning
confidence: 99%